Kristus i de dødes rige - et maleri og dets kontekst - Larsen, Peter Nørgaard (Grundtvig-Studier, 2001)
Joakim Skovgaard: Christ in the Realm of the Dead By Peter Nørgaard Larsen Without in any way pretending to envelop Joakim Skovgaard’s huge painting Christ in the Realm o f the Dead (1891-94) in an exhaustive monograph, the article attempts, in three main sections, origin, meaning, reception, to approach an understanding of the art-historical models and inspirations for the work, its possible meaning, and, finally, its reception and its chequered course through the history of Danish art. Origin The encounter with the archaic, .austere style. in both architecture, scuplture and in vase painting was of crucial significance for Skovgaard’s work. The simplicity in both the composition, the movements and expressions of the figures and also the frieze-like coordination of the figures characteristic of the .austere style. and to a large extent of the early Italian Renaissance - another important source of inspiration for Skovgaard’s art - has left crucial traces in Christ in the Realm o f the Dead. It can be seen in the grandiose simplicity of the composition, in its gesticulations and expressive power and in the powerful balance struck between the vertical and the horizontal, between figure and space. Joakim Skovgaard was very reticent with regard to lifting the veil on the thoughts and choices behind his magnum opus. Thus, the picture receives only few mentions in the artist’s letters. And here as in later interviews his virtually sole comment is that the motif was taken from his mother’s favourite hymn, Grundtvig’s rewriting from 1837 of Caedmon’s Anglo-Saxon poem, .The Harrowing of Hell: This night there was a knocking on the gates of Hell.. Meaning One thing that constantly makes itself felt is the vast size of the painting (351,5 x 489 cm). Had it been a commissioned work, most likely in the form of an altarpiece, this would explain the format. But as the painting was done on the artist’s own initiative and at his own expense, we can talk of a unique project in Danish art. Skovgaard clearly conceived of his work as an artist as a calling, and the task was to make great art work as convincingly as possible for God and the spreading of Christianity. As a deeply rooted personal testimony and as a reply to the materialism and and religious doubt of the time and the profanation of the figure of Christ, Skovgaard was re-installing Christ as the almighty, awesome power that can fight titanic battles for the sake of mankind. Skovgaard managed not only to create a picture with a rare power of conviction, but also to let his hero stand as a statement of how, on the threshold of the modern world, art is still able to generate an artistic statement that is both contemporary and relevant. The realm of the dead with the anonymous host of corpse-like beings, who after an age spent in spiritless darkness are forcing their way forward towards a liberating light, is perhaps Skovgaard’s allegory of the time’s doubt and uncertain groping for a spiritual base in the historical transition between tradition and modernity. Reception Among most young artists and critics, Skovgaard’s painting was pointed out as a milepost in Danish art, which set new standards for the strivings and potential of Danish art. The critics of the painting maintained that the work was unrealistic. The figures were far too rough and stiff and the out-pouring of emotion too overwhelming. After it had been moved around for several years, spending a short time in the Immanuel Church in Copenhagen, being accorded an enthusiastic reception in the Paris World Fair in 1900, and subsequently hanging in St.Olai Church in Helsingør (Elsinore), Statens Museum for Kunst decided to purchase the painting in 1911. The painting was exhibited in Statens Museum for Kunst until 1965, when, as a result of the re-building of the museum, it was rolled up and moved out along with the rest of the collection. When the museum reopened in 1970 it was not included among the works hung. Instead it was condemned to obscurity, i.e. kept rolled up in storage. Here it remained for 30 years until a major conservation project in 2000 gave the public and the art historians an opportunity to join in the debate on this epoch-making and much discussed painting.